Polski sektor energetyczny na tle krajów Unii Europejskiej w latach 1994-2002 - analiza porównawcza - Zawada, Marcin (Polish sector of power engineering in comparison with the European Union countries in the years 1994-2002 - comparative analysis, 2006)
This paper is aimed at determining the level of development of the Polish sector of power engineering in comparison with sectors of selected 15 countries of the European Union using methods of multivariate comparative analysis with special attention paid to cluster analysis, construction of taxonomic measure of development and specification of the time delay that is characteristic of the Polish sector of power engineering in comparison with its counterparts in the analyzed countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 326-334